Introducing Exchange-Rate Equations into a World Econometric Model. - Wren-Lewis, S (1987)
The National Institute of Economic and Social Research's world econimc forecasts are for the first time produced with the aid of a large quarterly econometric model. The model is based on the World Economic Prospects (WEP) model which has been operated and developed by economists in HM Treasury for more than a decade. However, exchange rates in WEP are exogenous, and this article discusses the estimation of an exchange-rate system for the model and its implications in terms of overall model properties.